The reporting of race and/or ethnicity in the medical literature: a retrospective bibliometric analysis confirmed room for improvement - Bokor-Billmann, Therezia; Langan, Ewan Andrew; Billmann, Franck (Journal of clinical epidemiology, 2020)
Objectives - Although the collection of race and/or ethnicity data is an important way to identify and address inequalities in health care provision and disparities in access to treatment, studies examining the extent to which race and/or ethnicity data are reported in the medical literature, and the quality of these data, are lacking. Therefore, we sought to objectively determine the quality of reporting of race and/or ethnicity in original medical research papers. - Study Design and Setting - A retrospective bibliometric analysis was used. Two independent investigators analyzed original articles investigating race/ethnicity, published between 2007 and 2018, in the 10 top-ranking academic journals in each of the following categories: general medicine, surgery, and oncology. - Results - A total of 995 original articles were included in our analysis. Only 45 studies (4.52%) provided a formal definition of race/ethnicity, and 8.94% identified the investigator responsible for the classification. While race/ethnicity was a key part of study design in 31.86% of the included investigations, the method used to classify individuals into racial/ethnic groups was described in only 10.25% of articles. In terms of terminology, we identified 81 different race/ethnicity classifications, but these were often imprecise and open to interpretation. - Conclusion - There is significant room for improvement in the collection, reporting, and publishing of data describing ethnicity and/or race in the medical literature.